Pemanfaatan Barang Bekas sebagai Sarana Peningkatan Soft Skills Siswa di SDI Buraen 2 - Brigita Veridiana BupuDaa; Siprianus Kiik; Indriyati Indriyati; Karolus Tatu Sius; Hendrikus Likusina Kaha (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
The low level of non-academic skills such as creativity, cooperation, and environmental awareness among students at SDI Buraen 2 demonstrates the importance of developing soft skills from an early age. Furthermore, household waste, which has the potential to be a learning medium, has not been optimally utilized. This community service program aims to improve students' soft skills through recycling education based on the use of used goods. The activity was implemented in three stages: socialization of the importance of recycling, training in creating crafts from used goods, and evaluation of student skills using observation and an assessment rubric. The results of the activity showed improvements in students' creativity, collaboration skills, and awareness of environmental cleanliness. This program serves as an example of contextual learning that is relevant to local conditions and effective in instilling character values and environmental awareness in elementary school students.